Ultrastructure and histochemistry of the mineral concretions in the midgut of bees (Hymenoptera: Apidae) - Da Cruz-Landim, Carminda [UNESP]; Serrão, Iosé Eduardo [UNESP] (Brill Academic Publishers, 1997)
Mineral concretions in the digestive cells of bees were examined under transmission electron microscope and histochemically. Ultrastructure shows two types of mineral deposits: 1) mineral concretions which are organized in granules with a striking concentrically layered organization of opaque and clear zones and 2) electron dense granules which appear inside small vacuoles (0.4-0.7 μm). These two structures are present in the apex of the digestive cells of the posterior midgut. Histochemical data reveal that mineral concretions are composed of calcium, iron and uric acid or its salts while calcium determination gives a positive reaction for electron dense granules. Morphological and chemical similarities between the mineral concretions of bees and those described for other insects suggest that they have an important physiological role regulating the composition of the internal environment and to avoid intoxication. Since concretions and granules are structurally distinct, it is suggested that they are functionally different.
Keywords: Bee; Histochemistry; Midgut; Mineral concretions; Spherites